2019
DOI: 10.3390/nu11051153
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Different Animal-Derived Protein Sources on Adiposity and Glucose Homeostasis during Ad Libitum Feeding and Energy Restriction in Already Obese Mice

Abstract: Low-fat diets and energy restriction are recommended to prevent obesity and to induce weight loss, but high-protein diets are popular alternatives. However, the importance of the protein source in obesity prevention and weight loss is unclear. The aim of this study was to investigate the ability of different animal protein sources to prevent or reverse obesity by using lean or obese C57BL/6J mice fed high-fat/high-protein or low-fat diets with casein, cod or pork as protein sources. Only the high-fat/high-prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…In line with human epidemiological studies [ 1 , 2 , 3 ] and earlier observations in mice [ 15 , 24 , 33 , 38 , 39 , 40 ], we here demonstrate that different protein sources exhibit profound differences in their ability to modulate obesity development. This study supports the notion that dietary proteins from marine sources are less obesogenic than protein from terrestrial sources [ 24 , 38 , 39 ]. Thus, mice fed the chicken-based diet gained more weight than mice fed the cod-based diet, whereas weight gain in mice fed the pangasius-based diet fell in between.…”
Section: Discussionsupporting
confidence: 91%
“…In line with human epidemiological studies [ 1 , 2 , 3 ] and earlier observations in mice [ 15 , 24 , 33 , 38 , 39 , 40 ], we here demonstrate that different protein sources exhibit profound differences in their ability to modulate obesity development. This study supports the notion that dietary proteins from marine sources are less obesogenic than protein from terrestrial sources [ 24 , 38 , 39 ]. Thus, mice fed the chicken-based diet gained more weight than mice fed the cod-based diet, whereas weight gain in mice fed the pangasius-based diet fell in between.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, Myrmel et al. (2019) reported that the intake of cod without fat removal had a decreased insulin sensitivity compared with the intake of casein in high‐fat/high‐protein diet fed obese mice during ad libitum feeding. Further research is needed to clarify the effect of dietary APP on insulin sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…The tremendous genetic diversity of the CC population (Philip et al, 2011 ; Collaborative Cross Consortium, 2012 ; Srivastava et al, 2017 ; Shorter et al, 2019 ) facilitates the discernment between effects caused by diet from effects caused by genetic variation when measuring differences and changes in adiposity and other metabolic traits across multiple genetic “replicates” in each strain, thereby increasing power, reproducibility, and relevance to obesity in humans (Mathes et al, 2011 ). Following a 2-week acclimation period on standard synthetic diet (AIN-76A) to determine baseline phenotypes, mice between 8 and 11 weeks of age were randomized and put on experimental diets (high fat high sucrose or high protein) for 8 weeks, followed by analysis of body composition, metabolic rate, clinical blood chemistries, and circulating metabolites to assess the effect of diet on each trait since diets with higher protein, low glycemic index, and lower fat content may assist in maintaining weight loss compared to diets with higher carbohydrate content (Abete et al, 2010 ; Larsen et al, 2010 ; Hu et al, 2018 ; Myrmel et al, 2019 ; San-Cristobal et al, 2020 ). While both genetics and diet interact to influence adiposity and other phenotypes, health outcomes were more strongly impacted by genetic effects than diet.…”
Section: Introductionmentioning
confidence: 99%